TRANSFORMATECH: INTERACTIVE LEARNING WEBSITE BASED ON CHALLENGE-BASED DIFFERENTIATED LEARNING INTEGRATED WITH SCRATCH FEATURING BATIK NUSANTARA TO OPTIMIZE STUDENTS' COMPUTATIONAL THINKING SKILLS - Resty Kartika Sari; Maylafayza Salsabila Zen; Danella Putri Wulandari; Cahya Sari Andiani; Avita Dewi Sila Wardani; Adi Satrio Ardiansyah (Prima: Jurnal Pendidikan Matematika, 2026)
Computational thinking (CT) has become a vital competence in mathematics education, yet students in Indonesia often demonstrate low proficiency in this area, particularly in abstraction and algorithmic thinking. This study aimed to develop a technological innovation named TransformaTech, an interactive learning website integrating the Challenge-Based Differentiated Learning model and Scratch programming featuring Batik Nusantara to optimize students’ CT skills. Applying the 4D development model, this research involved a population of 9th-grade students at SMP Negeri 13 Semarang for the 2025/2026 academic year. From this population, 29 students were selected through simple random sampling to serve as the experimental class. Data were collected using validation sheets, teacher practitioners' questionnaires, student response forms, and CT tests. The results indicated that TransformaTech was highly feasible, with an expert validation score of 85.72%, and highly practical, with a practitioner assessment of 90.63%. The media proved effective in improving students' CT skills, as evidenced by an N-Gain score of 0.6068, falling into the moderate category. Furthermore, students provided a highly positive response with an average score of 78.43%, highlighting the platform's ability to create an engaging learning environment.